Analysis Of Factors That Affect the Implementation Of Triage On Satisfaction Of Patients Family - Tariq Ullah (Chakra Brahmanda Lentera Institute, 2022)
Background: Error giving priority colors significantly affects patients' actions, speed, and family satisfaction. The problem of labeling colors that should be red to yellow labels will hinder patients from being treated. Errors in sorting emergency patients can be fatal to the speed and accuracy of medical and nursing interventions provided. This study aimed to determine the relationship between the accuracy of triage and the patient's family satisfaction in the Emergency Department. Methods: The design used in this study is Cross-Sectional. The population was all patients' families in the Emergency Department, with a total of 1122. The sample size was 113 respondents using the accidental sampling technique. The independent variable of research is the Accuracy of Triage Implementation. The dependent variable is Satisfaction. Data were collected using a questionnaire, then analyzed using the rho spearmint test with a significance level of α ≤ 0.05. Results: The results showed that nearly half of the respondents had an appropriate triage accuracy of 87 respondents (77%), and respondents had sufficient Satisfaction, as many as 50 respondents (44.2%). The statistical test in this study used the Spearmen's rho test with a <0.05 obtained p = 0,000 where H1 was accepted and H0 was rejected, which means there was a relationship between triage accuracy to the Family Satisfaction of Patients in the Emergency Department. Conclusion: The accuracy of triage towards family satisfaction of patients is essential to be improved to reduce errors and improve the quality of services. nurses can identify satisfaction factors in the ED